Pengaruh Pendekatan Deep Learning Malalui Model Problem Based Learning Terhadap Pemahaman Konsep Dan Kemampuan Pemecahan Masalah Dalam Pembelajaran Matematika - Asna Bariroh , Asna (Amaliyatu Tadris, 2025)
This study aims to determine the effect of implementing the Deep Learning approach through the Problem Based Learning (PBL) model on students’ conceptual understanding and problem-solving abilities in mathematics learning at MBI Amanatul Ummah Pacet. The Deep Learning approach was chosen because it encourages students to think deeply, connect concepts, and develop critical and reflective thinking skills. The research method used was a quasi-experimental design with a Pretest-Posttest Control Group Design. The subjects of the study consisted of 60 eleventh-grade students from MBI Amanatul Ummah Pacet, divided into two groups: an experimental group taught using the Deep Learning–PBL approach and a control group taught using conventional methods. The research instruments included a conceptual understanding test, a problem-solving ability test, observation sheets, and a student response questionnaire. Data were analyzed using the Independent Samples t-test with a significance level of 0.05. The results showed that there was a significant difference in learning outcomes between the experimental and control groups. Students who participated in learning using the Deep Learning–PBL approach showed a higher average improvement in both conceptual understanding and problem-solving abilities. Therefore, it can be concluded that the Deep Learning approach through the Problem Based Learning model has a positive and significant effect on improving mathematics learning outcomes and can create a more meaningful, active, and higher-order-thinking-oriented learning process.